APPRAISING HEAVY METALS AND IONIC SPECIES IN ROAD DUST OF YABA COLLEGE OF TECHNOLOGY CAMPUS AND ENVIRONS, LAGOS - NIGERIA (FULafia Journal of Science and Technology, 2026)
This study reports the concentrations of selected heavy metals (Zn, Pb, Cu, Ni, Cd) and ionic species (????????42−, ????????3−, Cl–, ????????32−, ????2????42−) in road dust samples within Yaba College of Technology and its surrounding environment in Lagos State, Nigeria. 44 dust samples were collected from January to June 2025, four times a month across eleven locations. Road dust were swept using a hand brush into plastic parkers and transferred into sterile valves. Samples were sieved through a 75-μm stainless steel mesh, weighed, and digested with nitric (HNO₃) and sulphuric (H₂SO₄) acids. Heavy metal concentrations were determined with an inductively coupled plasma-optical emission spectrometer (ICP-OES), while ionic species were analyzed using standard Analytical methods and procedures. The percentage contributions of contaminants were: Zn - (60.63%), Pb - (22.42 %), Cu (8.75 %), Cd -(1.01 %), Ni -(7.19 %); and among ionic species: ????????4− -(42.62 %), ????????3− -(21.90 %), Cl– -(12.07 %), ????????32− -(16.32 %), and ????2????42− -(7.09 %). Zinc -(1434.69 mg/kg), showed the highest metal concentration, whereas Cadmium - (23.89 mg/kg) had the lowest. Sulphate -(841.38) was the most abundant, while Oxalate- (139.89 mg/kg) was least. Principal Component Analysis (PCA) identified three components accounting for 86.68 % of the total variance, indicating anthropogenic influence. Pearson correlation analysis revealed significant positive relationship (p < 0.05) between metals and ionics species. Concentrations of Zn, Pb, Ni, and Cu exceeded limits set by the Federal Ministry of Environment, the European Communities, and United Nations Environmental Programme, confirming pollution in the study area
Keywords: pollution; dust; anthropogenic; sample; contamination; heavy metal